Theoretical Aspects of Entrepreneurial Education for Hospitality Industry - GORYUSHKINA, Natalia; VOINOVA, Natalia; VORONKOVA, Olga; SITNOV, Alexey; SHICHIYAKH, Rustem; GORDEYEVA, Olga (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.10.4(36).14, 2019)
Entrepreneurship is a professional employment within the framework of establishing and management of their own business based on the self-employment principle which targets on both providing and development of new benefits and values, manufacturing and sales of goods, execution of works and rendering services as well as creation and upkeeping of working places along with bearing social responsibility towards both the state and the society. Presently, education of hospitality industry entrepreneurs is rather a perspective scientific task. The author has considered theoretical aspects of education of the persons ready to start their entrepreneur’s activity in the field of hospitality industry, has identified the characteristic features of entrepreneurship in that area as well as the issues of services rendering at the confluence of material and non-material fields. Also, the author has underlined that to build up a successful career a future entrepreneur-hotelier shall form some basic qualities and develop abilities to self-organization and self-development.